Complications of invasive surgery for trigeminal neuralgia - Fedirko, V; Dubrovka, A; Luzan, B (Pain medicine, 2025)
Trigeminal neuralgia (TN) is a severe chronic condition characterized by acute pain that can lead to disability. For patients unresponsive to pharmacological therapy, surgical methods such as microvascular decompression (MVD), radiofrequency thermocoagulation, balloon compression, glycerol rhizotomy, or cryoablation are primary treatment options. However, each of these procedures carries specific risks of complications, including nerve damage, infections, hemorrhagic complications, pain recurrences, and method-specific side effects. This article presents the results of a retrospective analysis of 250 patients with TN. Complications following MVD were observed in 18 % of cases, including pleocytosis, dysesthesia, localized cerebellar ischemia, and facial nerve paresis. For percutaneous procedures, the complication rate reached 37 %, encompassing pain recurrence, dysesthesia, anesthesia dolorosa, and other adverse outcomes. The study emphasizes the importance of a multidisciplinary approach to prevent complications and to select the most suitable treatment method for each patient.